Behaviour in The Early Years - Glenn, Angela; Helps, Alicia; Cousins, Jacquie; Glenn, Angela (London : Routledge, 2010)
Written for practitioners who work in pre-school settings and parents, this work teaches how to respond instantly and effectively to problems using hands-on strategies. The book provides hands-on tried and tested strategies to help you respond instantly and effectively to behaviour problems.
Formerly CIP.
Keywords: Problem children -- Education (Preschool) -- England -- Medway; Education, Preschool -- England -- Medway